URGENSI HABITUASI BAGI ANAK DIDIK PAUD: The Urgency of Habituation for Early Childhood Education Students - Hidayatu Munawaroh; Robingun Suyud El Syam (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2025)
The habituation approach is very effective in the world of education in order to accustom students to repeatedly doing something so that it becomes a habit that is difficult to leave. The research aims to reveal the urgency of habituation for PAUD students. The article is the result of library research with a qualitative approach. The research findings show that implementing habituation consistently and in a structured manner for PAUD students can help children become individuals with character, discipline, and are ready to face challenges in the future. These findings reinforce the importance of habituation for early childhood education. The research recommends that it is important for PAUD managers to make habituation a focus of learning in order to form strong student character. The research provides direction for future research related to the focus of the urgency of habituation for students considering its importance for improving the quality of education, responding to moral degradation, the impact of uncontrolled globalization.